PENGGUNAAN ISTISHAB DAN PENGARUHNYA TERHADAP PERBEDAAN ULAMA - Husnul Haq (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2017)
Islam is a comprehensive religion. The comprehension of Islam does not lie in the completeness of the content of the Qur'an and Hadith, because in fact the verses of the Qur'an and Hadith are limited in number, while the human problems are growing. So, the role of ijtihad as a means of reform of Islamic law is vital. One of the methods of ijtihad is istishab. This study aims to describe the nature of istishab, clerical opinion about the value of its strength as a source of law, as well as the influence of ulama's opinion about the value of his resistance to differences of opinion in Islamic law. The approach used in this research is descriptive-qualitative. By using this method of research, this study concludes that the majority of scholars of the Maliki, Shafii, and Hambali sect assert that istishab is a hujjah to defend something that already exists (daf'i) and establish something that does not exist yet (itsbat). The late ulamas of the Hanafi sect assert that istishab is a hujjah in defense of something that already exists, while the majority of the Hanafi scholars and some scholars of the Shafi'i sect state that istishab is not a hujjah at all. The difference of the ulama's view of the use of istishab in ijtihad has led to differences in their views on Islamic law, as in the case of the law of the disappeared’s inheritance. Islam merupakan agama yang komprehensif. Komprehensifitas Agama Islam tidak terletak pada kelengkapan kandungan al-Qur’an dan Hadis, sebab faktanya ayat al-Qur’an dan hadis jumlahnya terbatas, sedangkan permasalahan manusia semakin kompleks. Karenanya, peran ijtihad sebagai sarana pembaharuan hukum Islam sangatlah vital. Salah satu metode ijtihad adalah istishab. Penelitian ini bertujuan untuk mendeskripsikan hakikat istishab, pendapat ulama tentang nilai kehujjahannya, serta pengaruh perbedaan pendapat ulama tentang nilai kehujjahannya terhadap perbedaan pendapat dalam hukum Islam. Pendekatan yang penulis gunakan dalam penelitian ini adalah deskriptif-kualitatif. Dengan menggunakan metode penelitian tersebut, penelitian ini menyimpulkan bahwa mayoritas ulama dari mazhab Maliki, Syafi’i, dan Hambali menyatakan bahwa istishab merupakan hujjah untuk mempertahankan sesuatu yang sudah ada (daf’i) dan menetapkan sesuatu yang belum ada (itsbat), sedangkan ulama Muta’akhirin dari mazhab Hanafi menegaskan bahwa istishab merupakan hujjah dalam mempertahankan sesuatu yang sudah ada saja, sementara mayoritas ulama mazhab Hanafi dan sebagian ulama mazhab Syafi’i menyatakan bahwa istishab bukan merupakan hujjah sama sekali. Perbedaan pandangan ulama tentang penggunaan istishab dalam ijtihad ini ternyata menyebabkan perbedaan pandangan mereka dalam hukum Islam, seperti dalam kasus hukum waris orang hilang.